Aspects Didactiques de l’Éducation Bilingue Français-Langues Africaines au Mali - Maurer, Bruno (Papers from the Annual Meetings of the Atlantic Provinces Linguistic Association (PAMAPLA) / ACTES DES COLLOQUES ANNUELS DE L’ASSOCIATION DE LINGUISTIQUE DES PROVINCES ATLANTIQUES (ACAALPA)., 2006)
The purpose of this article is to suggest a concrete plan of action concerning bi- and plurilingual education. The article’s suggestions are based on a two-year collaborative project with the Ministère de l ’Éducation nationale du Mali. Original solutions are proposed to implement the bilingual education model retained by national policy. The objective of the project is to answer a two-fold question: How do we help students to learn French better while teaching them the national language? How do we take into account national language acquisition while teaching French? The recommended model is based on the principles of convergent pedagogy, an active language learning method that seeks to develop functional bilingualism. A few educational tools are appended to this article. Résumé Cet article propose des pistes d ’action concrètes en matière d’éducation bi- ou plurilingue en s’appuyant sur l’expérience d’une collaboration de deux ans au sein du Ministère de l’Éducation nationale du Mali. Il présente les solutions originales proposées pour incarner le modèle d’éducation bilingue choisi par les politiques nationaux. Le projet avait pour but de répondre à deux questions complémentaires : comment enseigner la langue nationale aux élèves de telle sorte que l’apprentissage du français s’en trouve facilité et comment enseigner le français en prenant en compte les acquis dans la langue nationale? Le modèle proposé se fonde sur les principes de la pédagogie convergente. Quelques outils pédagogiques sont fournis en annexe.